Iterative methods for the solution of the phase problem in protein crystallography - Thumiger, Anton; Zanotti, Giuseppe (2009)
Summary: The phase problem is a major challenge when using X-ray crystallography for structure de-termination. This is especially true when the objects studied are macromolecular crystals, which contain many atoms and diffract quite poorly. For this reason, conventional direct methods, which are very successful for small and medium-sized molecule crystals, generally fail with protein crystals that do not diffract to atomic resolution. In this paper, we review some of the iterative phase retrieval methods used in optics, and present our own results obtained while trying to extend these methods to the field of macro-molecular crystallography. A binary constraint on density has been incorporated in a new iterative algorithm, as well as into an existing Difference Map, in order to attempt crystallographic phase retrieval. Another existing algorithm, Charge Flipping, has been modified to test a connectivity-based phasing approach. While the results on binary densities could not be extended to realistic cases, the connectivity criterion has shown to possess some phase extension power
Bibliografija: 13 jed
Keywords: Rentgenska difrakcija -- Elektronska gustoća -- Kristalna struktura -- Proteini -- Iterativna metoda